THE ROLE OF THE VILLAGE SECRETARY IN PLANNING APBDES IN TOLONDADU I VILLAGE, BOLAANG UKI SUB-DISTRICT SOUTH BOLAANG MONGONDOW DISTRICT - Usman Kumedi; Sitti Husna; Darman (Journal of Governance and Global Studies, 2024)
The study aims to determine the role of the Village Secretary in Planning the Village Income and Expenditure Budget in Tolondadu I Village, Bolaang Uki District, South Bolaang Mongondow Regency. This research uses a qualitative descriptive approach. Data sources used in qualitative writing are primary and secondary data sources.The results can be concluded that the Village Secretary has a significant role in Village Revenue and Expenditure Budget Planning; there needs to be attention from the leadership regarding the importance of improving performance or skills to maximize the Village secretary’s duties in carrying out his work. The provision of facilities and infrastructure also needs to be enhanced to support the performance of the Village Secretary, especially in Village Revenue and Expenditure Budget Planning.